Exploring the Potential of Metaverse Apps for Real-World Applications: A Case Study with CALEND_AR - Tsomokos, Konstantinos; Sintoris, Christos; Fidas, Christos; Avouris, Nikolaos (Springer Nature Switzerland, 2023)
This paper presents CALEND_AR, a hybrid calendar application that uses augmented reality technologies to blend physical and digital calendars. The study investigates user preferences and motivations for using physical or digital calendars and explores the need for a hybrid solution that incorporates both. It comprehensively describes the application’s implementation process, including technological background, design considerations, and a user study. Evaluation results show that the hybrid approach combining the benefits of paper-based and digital calendars was appreciated by participants, despite limitations such as inconsistent accuracy of text recognition and mixed user reception of the augmented reality feature. The contributions of the work include the development of a unique and innovative hybrid approach to calendar management and demonstrating the potential of metaverse apps to address real-world problems and enhance people’s lives. Future research could explore ways to improve text recognition accuracy and make the augmented reality feature more user-friendly. Overall, CALEND_AR represents an important step forward in designing augmented and mixed reality applications.
Keywords: Augmented Reality; Calendar Management; Digital Calendar; Hybrid Calendar; Paper-Based Calendar; Text Recognition; User Evaluation